3D PRINTING TECHNOLOGY IN HUMAN ANATOMY MODERN TEACHING AND LEARNING - Kazoka, Dzintra; Pilmane, Mara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
There are various combinations of 3D printing technology and medical study process. The aim of this study was to summarize our first experience on 3D printing and outline how 3D printed models can be successfully used in Human Anatomy modern teaching and learning. In 2018 autumn semester, together with traditional methods, a three-dimensional (3D) printing has been introduced into Human Anatomy curriculum at Department of Morphology. In practical classes 39 groups of students from Faculty of Medicine 1st year together with 3 tutors used 3 different open source softwares to create anatomical models and prepared them for printing process. All anatomical models were produced using an FDM 3D printer, a Prusa i3 MK2 (Prusa Research). As methods for data collection were used our observational notes during teaching and learning, analysis of discussions between tutors and students, comments on the preparing and usability of the created and printed models. 3D printing technology offered students a powerful tool for their teaching, learning and creativity, provided possibility to show human body structures or variations. Presented data offered valuable information about current situation and these results were suitable for the further development of the Human Anatomy study course.